Use of social media Edmodo in secondary education subjects: Biology and Geology - Antonio Rodríguez Ruibal; Miguel Iglesias Vegas (Centro de Estudios Financieros, 2016)
Social media have become one of the most powerful and innovating tools to encourage collaborative work and lifelong learning. This study shows the result obtained after using the social network Edmodo when teaching in a high school of Asturias. We intend to analyse the degree of student ́s acceptance of this blended learning strategy. This technology allows us take the teaching and learning process beyond the classroom space increasing the adquisition of knowledge and basic skills.